Realitas Prinsip Piercing The Corporate Veil dalam Mewujudkan Good Corporate Governance - Iqlima Thahirah; Maulidhina Amalia Fauziah; Sumriyah Sumriyah (Jurnal Hukum dan Sosial Politik, 2023)
. The purpose of this article is to establish the development of the legal theory and doctrine of Piercing The Corporate Veil in the law on limited liability companies. The legal reform of legal persons can be traced back to two milestones in the history of legal persons, namely, firstly, the emergence of the theory of legal persons, which focuses on the personalization of legal persons as if they were persons, and secondly, the emergence of the corporate law doctrine known as Piercing the Corporate Veil, which is motivated to reveal the legal veil of the persons behind the company, namely, shareholders, directors and managers. The research method is normative law with a normative approach), concepts and cases. The results of this study can be attributed to the fact that the principle of piercing the corporate veil supports the implementation of the GCG to prevent the abuse of shareholder power. The principle of piercing the corporate veil can limit or prevent unlawful acts committed by shareholders, commissioners and directors who exploit corporate opportunities for personal gain or misuse of corporate assets. The conclusion of this study is that the legal effect of the principle of piercing the corporate shield on the liability of the PT, if violated, has the effect of limiting the liability of the company to unlimited liability (unlimited liability) up to the personal assets of the shareholders.